Higher Maternal Dietary Protein Intake Is Associated with a Higher Risk of Gestational Diabetes Mellitus in a Multiethnic Asian Cohort. Issue 4 (8th March 2017) - Pang, Wei Wei; Colega, Marjorelee; Cai, Shirong; Chan, Yiong Huak; Padmapriya, Natarajan; Chen, Ling-Wei; Soh, Shu-E; Han, Wee Meng; Tan, Kok Hian; Lee, Yung Seng; Saw, Seang-Mei; Gluckman, Peter D; et al.
Abstract: Background: Dietary protein may affect glucose metabolism through several mechanisms, but results from studies on dietary protein intake and risk of gestational diabetes mellitus (GDM) have been inconsistent. Objective: We examined the cross-sectional associations of dietary protein intake from different food sources during pregnancy with the risk of GDM in a multiethnic Asian population. Methods: We included 980 participants with singleton pregnancies from the Growing Up in Singapore Toward healthy Outcomes (GUSTO) cohort. Protein intake was ascertained from 24-h dietary recall and 3-d food diaries at 26–28 wk gestation. GDM was defined as fasting glucose ≥7.0 mmol/L and/or 2-h postload glucose ≥7.8 mmol/L at 26–28 wk gestation. We evaluated the association of dietary protein intake with GDM risk by substituting carbohydrate with protein in an isocaloric model with the use of multivariable logistic regression analysis. Results: The prevalence of GDM was 17.9% among our participants. After adjustment for potential confounders, a higher total dietary protein intake was associated with a higher risk of GDM; the OR comparing the highest with the lowest quartile of intake was 2.15 (95% CI: 1.27, 3.62; P -trend = 0.016). Higher intake levels of both animal protein (OR: 2.87; 95% CI: 1.58, 5.20; P -trend = 0.001) and vegetable protein (OR: 1.78; 95% CI: 0.99, 3.20; P -trend = 0.009) were associated with a higher risk of GDM. Among the animal protein sources, higher intake levels of seafood protein (OR: 2.17; 95% CI: 1.26, 3.72; P -trend = 0.023) and dairy protein (OR: 1.87; 95% CI: 1.11, 3.15; P -trend = 0.017) were significantly associated with a higher GDM risk. Conclusion: Higher intake levels of both animal and vegetable protein were associated with a higher risk of GDM in Asian women. This trial was registered at clinicaltrials.gov as NCT01174875.